Tantric teachings of the Kālikā Purāṇa - Kooij, Karel R. van (Brill's Indological library, 2022)
"At a lonely place, in a remote hermitage somewhere in the Himālaya, the god Śiva is teaching Tantric worship to his humiliated sons, who want to regain their divine status: "You should worship the goddess Mahāmāyā Kālikā". Remarkable are his 'talks' about preliminary rituals, mudrās, and animal as well as human sacrifice. The Tantric Teachings form the inner core of the Kālikā Purāna, i.e. 'Old Stories about Kālikā', composed by a learned Brāhmin about a thousand years ago in Kāmarūpa (Assam). Careful listening to the text has been my first priority when presenting the relevant passages in text and translation"--